BEBIG 60Co HDR brachytherapy source dosimetric parameters validation using GATE Geant4-based simulation code. Issue 3 (March 2022) - Joya, Musa; Nedaie, Hassan Ali; Geraily, Ghazale; Ghorbani, Mahdi; Sheikhzadeh, Peyman; Arani, Mahmud Naraqi
Abstract: Purpose: This study aims to validate the dosimetric characteristics of High Dose Rate (HDR) 60 Co source (Co0.A86 model) using GATE Geant4-based Monte Carlo code. According to the recommendation of the American Association of Physicists in Medicine (AAPM) task group report number 43, the dosimetric parameters of a new brachytherapy source should be verified either experimentally or by Monte Carlo calculation before clinical applications. The validated 60 Co source in this study will be used for the simulation of intensity-modulated brachytherapy (IMBT) of vaginal cancer using the same GATE Geant4-based Monte Carlo code in the future. Materials and methods: GATE (version 9.0) simulation code was used to model and calculate the required TG-43U1 dosimetric data of the 60 Co HDR source. DoseActors were defined for calculation of dose rate constant, radial dose function, and anisotropy function in a water phantom with an 80 cm radius. Results: The dose rate constant was obtained as 1.070 ± 0.008 cGy . h − 1 . U − 1 which shows a relative difference of 2.01% compared to the consensus value, 1.092 ​cGy . h − 1 . U − 1 . The calculated results of anisotropy and radial dose functions starting from 0.1 cm to 10 cm around the source showed excellent agreement with the results of published studies. The mean variation of the radial dose and anisotropy functions values from the consensus data were 1% and 0.9% respectively. Conclusion: Findings from this investigation revealed that the validation of the HDR 60 Co source is feasible by the GATE Geant4-based Monte Carlo code. As a result, the GATE Monte Carlo code can be used for the verification of the brachytherapy treatment planning system. Abstract : GATE Monte Carlo code; HDR 60 Co source; TG-43 dosimetric parameters.